2008
DOI: 10.1007/s11295-008-0179-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in Eucalyptus nitens pulpwood and wood shrinkage traits

Abstract: Eucalyptus nitens plantations are generally established for pulpwood production but an increasing area is being managed for solid wood. Genetic variation in, and correlations among, three Kraft pulpwood traits (diameter at breast height, basic density and near-infrared-predicted cellulose content) and three 12-mm wood-core shrinkage traits (recoverable collapse, net shrinkage and gross shrinkage) were examined, utilising data from two 9-year-old firstgeneration progeny trials in Tasmania. These trials containe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 17 publications
7
28
0
1
Order By: Relevance
“…Density, diameter at age 2 (growth), volumetric shrinkage, acoustic velocity and stiffness all have significantly large heritability, suggesting that breeding for these traits is achievable. The heritabilities are similar to those reported for other eucalypt species (Hung et al 2014;Hein et al 2012;Blackburn et al 2010;Blackburn et al 2014;Hamilton et al 2008). Wood processors pay premiums for stable and stiff timber, while forest growers often prefer to have fastgrowing trees as to shorten rotation lengths increasing profitability.…”
Section: Resultssupporting
confidence: 75%
“…Density, diameter at age 2 (growth), volumetric shrinkage, acoustic velocity and stiffness all have significantly large heritability, suggesting that breeding for these traits is achievable. The heritabilities are similar to those reported for other eucalypt species (Hung et al 2014;Hein et al 2012;Blackburn et al 2010;Blackburn et al 2014;Hamilton et al 2008). Wood processors pay premiums for stable and stiff timber, while forest growers often prefer to have fastgrowing trees as to shorten rotation lengths increasing profitability.…”
Section: Resultssupporting
confidence: 75%
“…Basic density was assessed using the water displacement method [34]. At Meunna and Tarraleah basic density was assessed on 12 mm radial wood cores extracted from trees at a height of 0.9 m (core basic density) at age nine years [35] (Table 2). At Tarraleah and Southport, disks approximately 50 mm thick were extracted at a height of 5.8 m from the same trees assessed for AWV at ages 13 and 14 (Tarraleah), and 19 years (Southport) respectively.…”
Section: Eucalyptus Nitens Progeny Trialsmentioning
confidence: 99%
“…For Pinus pinaster Ait and Pinus taeda, Isik et al [52], Perez et al [34] and Gaspar et al [35] showed NIR as a potential tool to estimate heritabilities and genetic correlations for tree selection in physical and chemical properties. For Eucalyptus globulus and Eucalyptus nitens, the application of NIR focused on predicting the genetic parameters for cellulose [28,33], pulp yield [12,30,31], lignin [29]. Schimleck et al [15,32] investigated the cellulose content predicted with a NIR calibration model as an alternative to estimate Kraft pulp yield in Eucalyptus nitens.…”
Section: Genetic Parameters and Environmental Controlmentioning
confidence: 99%